Impact of Preoperative and Incident Musculoskeletal Problematic Areas on Postoperative Outcomes After Total Knee Replacement. Issue 9 (28th July 2021) - Zhang, MaryAnn; Selzer, Faith; Losina, Elena; Collins, Jamie E.; Katz, Jeffrey N.
Abstract : Objective: To examine impact of pre‐existing and incident problematic musculoskeletal (MSK) areas after total knee replacement (TKR) on postoperative 60‐month Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain/function scores. Methods: Using data from a randomized controlled trial of subjects undergoing TKR for osteoarthritis, we assessed problematic MSK areas in six body regions before TKR and 12, 24, 36, and 48 months after TKR. We defined the following two variables: 1 ) density count (number of problematic MSK areas occurring after TKR; range 0‐24) and 2 ) cumulative density count (problematic MSK areas both before and after TKR, categorized into four levels: no preoperative areas and density count of 0‐1 [reference group]; no preoperative areas and density count of 2 or more; one or more preoperative areas and density count of 0‐1; and one or more preoperative areas and density count of 2 or greater). We evaluated the associations between categorized 60‐month WOMAC and cumulative density count by ordinal logistic regression. Results: Among 230 subjects, 24% reported one or more preoperative problematic MSK area. After TKR, 75% reported a density count of 0 to 1; 25% reported a density count of 2 or more. Compared with the reference group, each cumulative density count category was associated with an increased odds of having a higher category of 60‐month WOMAC pain score, as follows: 2.97 (95% confidence interval [CI], 1.48‐5.98) for no preoperative problematic areas and density count of 2 or greater, 3.31 (95% CI, 1.64‐6.66) for one or more preoperative problematic areas and density count of 0 to 1, and 2.85 (95% CI, 0.97‐8.39) for one or more preoperative problematic areas and density count of 2 or greater. Similar associations were observed with 60‐month WOMAC function score. Conclusion: In TKR recipients, the presence of problematic musculoskeletal areas beyond the index knee—preoperatively and/or postoperatively—was associated with worse 60‐month WOMAC pain/function score.